Animal husbandry strategies in Eastern Zhou China: An isotopic study on faunal remains from the Central Plains. (23rd April 2018) - Zhou, L.; Hou, Y.; Wang, J.; Han, Z.; Garvie‐Lok, S.J.
Abstract: Textual records and archaeological evidence reflect prosperous animal farming in the Eastern Zhou of ancient China (770–220 BC ), but knowledge of how these animals were fed is limited. Here, we present the first stable isotopic study investigating animal husbandry strategies of this period. Isotopic features of faunal remains of 5 species discovered in Songzhuang cemetery suggest that pigs and dogs were fed on mixed diets with substantial internal variation, and cattle were fed mainly on a C4 ‐based diet. This is similar to the situation found in another Eastern Zhou cemetery, Tianli. Evidence from the 2 sites demonstrates that domesticated omnivores were raised in quite flexible ways, but cattle raising practices show consistency in different areas of China's Central Plains. Inter‐burial analysis of isotopic data suggests a very small scale of cattle farming during this period. Temporal comparison reveals that early Bronze Age people on the Plains had already established practices of provisioning cattle with C4 plants, and that these practices were inherited by Eastern Zhou people without significant change. However, manuring practices of the historical period likely elevated stable nitrogen isotope values of cattle slightly relative to Bronze Age values. This study sheds light on animal management practices on the plains during early historical times, and also provides faunal isotopic values for reference in studies of contemporary human diets.